Valoración de opciones reales a través de equivalentes de certeza (2014)
This purpose of this research is to identify appropriate rates to discount the flows from real options in situations in which the risk-free rate does not apply, in particular, in incomplete markets.  A methodology is proposed for valuing real options based on certainty equivalence, which requires as a principal condition the consideration of preferences represented with utility functions.  A constant relative risk aversion (CRRA) utility function is used to represent these preferences. The results indicate that this methodology adequately reflects how the value of a real option changes in accordance with an investor´s preferences.